The anti-inflammatory activity of peptides from simulated gastrointestinal digestion of preserved egg white in DSS-induced mouse colitis. Issue 12 (21st November 2018) - Zhang, Mengya; Zhao, Yan; Wu, Na; Yao, Yao; Xu, Mingsheng; Du, Huaying; Tu, Yonggang
Abstract : Peptides DEDTQAMPFR (DR-10), MLGATSL (ML-7), SLSFASR (SR-7), and MSYSAGF (MF-7) derived from simulated gastrointestinal digestion of preserved egg white (SGD-PEW) exerted anti-inflammatory effects on DSS-induced mouse colitis. Abstract : Peptides DEDTQAMPFR (DR-10), MLGATSL (ML-7), SLSFASR (SR-7), and MSYSAGF (MF-7) derived from simulated gastrointestinal digestion of preserved egg white (SGD-PEW) exerted anti-inflammatory effects on Caco-2 cells. Here, we aimed to evaluate the anti-inflammatory effects of these peptides derived from SGD-PEW in a mouse model of dextran sodium sulfate (DSS)-induced colitis. The results showed that DR-10, ML-7, SR-7 and MF-7 significantly ameliorated the clinical symptoms of DSS-induced mice colitis, such as weight loss, disease activity index (DAI), colon shortening, spleen hypertrophy and histological scores. Treatment with DR-10, ML-7, SR-7 and MF-7 also significantly inhibited the local secretion of pro-inflammatory cytokines TNF-α and IL-6 and markedly decreased the gene expression of pro-inflammatory cytokines, including TNF-α, IL-6, IL-17, IL-1β, IFN-γ and MCP-1, in DSS-induced mice colitis. Overall, MF-7 showed the best effect of alleviating DSS-induced colitis among the four peptides. These results suggested that MF-7, DR-10, ML-7 and SR-7 may be a potential promising candidate for the treatment of inflammatory bowel disease (IBD).